Crawling Predicts Infants' Understanding of Agents' Navigation of Obstacles. (15th May 2015) - Brand, Rebecca J.; Escobar, Kelly; Baranès, Adrien; Albu, Amanda
<x xml:space="preserve">Abstract</x> We investigated whether crawling versus noncrawling infants interpret an agent's movements around an obstacle as goal‐directed. Infants (6–9 months) were habituated to a self‐propelled circle jumping over an obstacle to reach a goal. When the obstacle was removed, infants who crawled (n = 13) showed longer looking time to the familiar but now nonrational jumping path versus a novel but rational straight‐line path. Noncrawlers (n = 17) did not discriminate. Looking preference was independent of age and speed of habituation. These findings support the claim that infants' processing of agency emerges early and applies to all agents, but stress the role of experience in the development of action interpretation.